2015
DOI: 10.1128/mbio.00308-15
|View full text |Cite|
|
Sign up to set email alerts
|

Complete Bypass of Restriction Systems for Major Staphylococcus aureus Lineages

Abstract: Staphylococcus aureus is a prominent global nosocomial and community-acquired bacterial pathogen. A strong restriction barrier presents a major hurdle for the introduction of recombinant DNA into clinical isolates of S. aureus. Here, we describe the construction and characterization of the IMXXB series of Escherichia coli strains that mimic the type I adenine methylation profiles of S. aureus clonal complexes 1, 8, 30, and ST93. The IMXXB strains enable direct, high-efficiency transformation and streamlined ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
197
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(211 citation statements)
references
References 45 publications
(58 reference statements)
0
197
0
Order By: Relevance
“…A chromosomal region encompassing atpA was PCR amplified from WT S. aureus JE2 chromosomal DNA using primer pair: 5′-ATATGAGCTCGAAGAGTTAGATAAGATTGTCAAACTAG-3′/5′-GATACAAGATCTGATGGTTTGTATTGCTACTTGC-3′ and cloned into pBASE6 via SacI/BglII. This plasmid was purified from E. coli IM08B (Monk et al, 2015) and transformed directly into JE2 atpA ::ΦNΣ (NE592) at 30°C followed by chromosomal integration by plating on TSA (10 μg/ml chloramphenicol) at 44°C overnight. Plasmid cross-out was performed by passage at 30°C followed by plating on TSA (500 ng/ml anhydrotetracycline) and successful allelic exchange of the transposon insertion with the intact atpA gene was selected for by replica plating of colonies and screening for sensitivity toward erythromycin and chloramphenicol.…”
Section: Methodsmentioning
confidence: 99%
“…A chromosomal region encompassing atpA was PCR amplified from WT S. aureus JE2 chromosomal DNA using primer pair: 5′-ATATGAGCTCGAAGAGTTAGATAAGATTGTCAAACTAG-3′/5′-GATACAAGATCTGATGGTTTGTATTGCTACTTGC-3′ and cloned into pBASE6 via SacI/BglII. This plasmid was purified from E. coli IM08B (Monk et al, 2015) and transformed directly into JE2 atpA ::ΦNΣ (NE592) at 30°C followed by chromosomal integration by plating on TSA (10 μg/ml chloramphenicol) at 44°C overnight. Plasmid cross-out was performed by passage at 30°C followed by plating on TSA (500 ng/ml anhydrotetracycline) and successful allelic exchange of the transposon insertion with the intact atpA gene was selected for by replica plating of colonies and screening for sensitivity toward erythromycin and chloramphenicol.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work with S. aureus has shown that lineages from different clonal complexes of S. aureus express divergent HsdS enzymes recognizing different TRMs (24). In agreement with that observation, we found that this is also the case with S. epidermidis because RP62A (CC10), NIH051475 (CC89), and NIH04008 (CC2) express divergent hsdS genes that specify different TRMs, while NIH051475 and VCU036, both of which belong to CC89, exhibit identical TRMs for the type I RM system (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of E. coli was performed with a standard heat shock protocol. S. aureus was transformed with electroporation using plasmid DNA isolated from E. coli DC10B (Monk et al, 2012) or IM08B (Monk et al, 2015). Preparation of electrocompetent cells and electroporation were performed essentially as described before (Lofblom et al, 2007).…”
Section: Bacterial Strains Growth Conditions and Transformationmentioning
confidence: 99%